Effects of high angular momentum on the unimolecular dissociation of CD2CD2OH: theory and comparisons with experiment. - McKown, BG; Ceriotti, M; Womack, C; Kamarchik, E; Butler, L; Bowman, J (2013)
This paper explores the dynamics of a highly rotationally and vibrationally excited radical, CD2CD2OH. The radical is produced from the 193 nm photodissociation of 2-bromoethanol-d4, so it is imparted with high angular momentum and high vibrational energy and subsequently dissociates to several product channels. This paper focuses on characterizing its angular momentum and modeling its effect on the product channels, including the HOD + vinyl-d3 product channel resulting from a frustrated dissociation of the radical originally en route to OH + ethene-d4 that instead results in D atom abstraction. Our impulsive model of the initial photodissociation shows that, for some cases, upward of 200 au of angular momentum is imparted, which greatly affects the dynamics of the competing product channels. Using a permutationally invariant potential energy surface and quasiclassical trajectories, we simulated the dissociation dynamics of CD2CD2OH and compared these results to those of Kamarchik et al. (J. Phys. Chem. Lett. 2010, 1, 3058-3065), who studied the dynamics of CH2CH2OH with zero angular momentum. We found that the recoil translational energy distribution for radicals that dissociated to OH + C2D4 matched experiment closely only when high angular momentum of the initial radical was explicitly included in the trajectory calculations. Similarly, the rate constant for dissociation changes when rotational energy was added to the vibrational energy in the initial conditions. Lastly, we applied the sketch-map dimensionality reduction technique to analyze mechanistic information leading to the vinyl + water product channel. Projecting the ab initio intrinsic reaction coordinates onto the lower dimensional space identified with sketch map offers new insight into the dynamics when one looks at the simulated trajectories in the lower dimensional space. Further analysis shows that the transition path resembles a frustrated dissociation of the OH + ethene radical adduct, followed instead by branching to vinyl + water when the leaving OH group encounters a nearby D atom on the ethene moiety. This characterization is in accord with the one made previously. We show that the transition path bifurcation between the two similar channels occurs at carbon-oxygen distances and oxygen-abstracted deuterium distances of 2-2.5 Å controlled by the C-O-D bond angle with large angles preferentially branching to the water plus vinyl product state. The experimental branching ratios were not reproduced by theory, however, due partly to the insufficient quality of the fitted potential surface. We also have evidence of a minor product channel, HD + vinoxy-d3, from our molecular dynamics simulations that allows us to assign the HD signal in prior experimental work.